2023
DOI: 10.3390/rs15092418
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation Characteristics of Groundwater Storage and Its Driving Factors and Ecological Effects in Tibetan Plateau

Wenhao Ren,
Yanyan Gao,
Hui Qian
et al.

Abstract: Known as the “Asian Water Tower”, the Tibetan Plateau (TP) is a rich water resource and serves an important ecological function. Climate change may cause changes to the water cycle, and these changes may affect the alpine vegetation growth. However, the variation characteristics of groundwater storage (GWS) and its driving factors and associated ecological effects in the TP are poorly understood. In this study, terrestrial water storage changes retrieved by GRACE (Gravity Recovery and Climate Experiment) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…After the water evaporates, salinity accumulates in the surface soil, which easily causes soil salinisation [70]. On the other hand, following an excessive decrease in groundwater, the efficiency of plant roots in absorbing and utilising groundwater is reduced, and vegetation cannot obtain enough SM [71]. Consequently, the regional vegetation cover is reduced, and the soil structure is loosened, which renders it susceptible to soil degradation and desertification.…”
Section: Concealed Risks Of Groundwater Recharge In Dryland Degradationmentioning
confidence: 99%
“…After the water evaporates, salinity accumulates in the surface soil, which easily causes soil salinisation [70]. On the other hand, following an excessive decrease in groundwater, the efficiency of plant roots in absorbing and utilising groundwater is reduced, and vegetation cannot obtain enough SM [71]. Consequently, the regional vegetation cover is reduced, and the soil structure is loosened, which renders it susceptible to soil degradation and desertification.…”
Section: Concealed Risks Of Groundwater Recharge In Dryland Degradationmentioning
confidence: 99%
“…Wei et al [15] investigated the relationships between fourteen landscape patterns and four hydrological indices for ten watersheds in the TP and found that runoff increases when a watershed is dominated by a small patch of landscape. Regarding the variability in groundwater storage, Ren et al [16] reported that the groundwater storage of the TP decreased at an average rate of −0.89 mm/a from January 2003 to December 2021. However, since January 2016, it has gradually recovered at a rate of 1.47 mm/a.…”
Section: Overviewmentioning
confidence: 99%
“…However, since January 2016, it has gradually recovered at a rate of 1.47 mm/a. It was found that the rising temperature may result in an increase in groundwater storage in regions where glaciers are distributed [16].…”
Section: Overviewmentioning
confidence: 99%